Tropical spastic paraparesis in Northeastern Brazil - C. M. de Castro Costa; M. R. Salgueiro; H. Carton; O. C. do Vale; A. M. de Arruda (Arquivos de Neuro-Psiquiatria)
Ten possible cases of tropical spastic paraparesis (TSP) in Northeastern Brazil (Ceará) are presented. They show the typical symptoms and signs of TSP consisting of weakness of the lower limbs, spastic gait, hiperreflexia, bladder dysfunction and variable signs of posterior columns impairment. The laboratory examinations excluded other compressive, infective, degenerative or demyelinating lesions of their spinal cord. Our patients age ranged from 21 to 59 years, all were of black origin and all were of lower social class. There was a slight preponderance of females. An etiological implication of a retrovirus (HTLV-I) has been shown for TSP, but for lack of technical conditions we could not determine it in our patients, and that stands as our subsequent step in those and further cases.